Why are women working so much more in Canada? : an international perspective - Tsounta, Evridiki (IMF working paper ;, 2006)
This paper analyzes the role of the tax and benefit system in spurring the impressive increase in Canadian female labor participation in the last decade. Using annual panel data for 10 large industrial countries over the period 1980-2001, I find that reforms in the Canadian tax and benefit system in the mid-1990s account for at least one-third of the observed increase in female participation in the period 1995-2001. The analysis indicates that policy initiatives similar to the "family-friendly" policies introduced in Canada could boost female participation in other countries and help policymakers meet the challenges of population aging